The recent progress of myeloid‐derived suppressor cell and its targeted therapies in cancers - Ruiyang Ren; Chenyi Xiong; Runyu Ma; Yixuan Wang; Tianyang Yue; Jiayun Yu; Bin Shao (MedComm, 2023)
Abstract Myeloid‐derived suppressor cells (MDSCs) are an immature group of myeloid‐derived cells generated from myeloid cell precursors in the bone marrow. MDSCs appear almost exclusively in pathological conditions, such as tumor progression and various inflammatory diseases. The leading function of MDSCs is their immunosuppressive ability, which plays a crucial role in tumor progression and metastasis through their immunosuppressive effects. Since MDSCs have specific molecular features, and only a tiny amount exists in physiological conditions, MDSC‐targeted therapy has become a promising research direction for tumor treatment with minimal side effects. In this review, we briefly introduce the classification, generation and maturation process, and features of MDSCs, and detail their functions under various circumstances. The present review specifically demonstrates the environmental specificity of MDSCs, highlighting the differences between MDSCs from cancer and healthy individuals, as well as tumor‐infiltrating MDSCs and circulating MDSCs. Then, we further describe recent advances in MDSC‐targeted therapies. The existing and potential targeted drugs are divided into three categories, monoclonal antibodies, small‐molecular inhibitors, and peptides. Their targeting mechanisms and characteristics have been summarized respectively. We believe that a comprehensive in‐depth understanding of MDSC‐targeted therapy could provide more possibilities for the treatment of cancer.